Green, Biodegradable, and Flexible Resistive Heaters-Based Upon a Novel Laser-Induced Graphene Manufacturing Process - Morais, Rogério Miranda [UNESP]; Vieira, Douglas Henrique [UNESP]; Ozório, Maiza da Silva [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Rollo, Andrew; Kettle, Jeff; Alves, Neri [UNESP] (Wiley, 2024)
Laser induced graphene (LIG), prepared directly with an in situ synthesis method onto Kraft Paper substrates, is proposed for the manufacture of biodegradable electronic devices. The investigation explores the influence of laser power and scanning speed on the properties of LIG conductive tracks and a sheet resistance of up to 0.25 kΩ sq−1. Raman spectroscopy and microscopy is used to analyse the interfacial properties, in particular the transition of cellulose fibers to carbonized graphene flakes through photothermal pyrolysis, leading to the formation of coral-like structures. To demonstrate the applicability of the approach, flexible resistive heaters have been manufactured and tests show rapid heating with a homogeneous distribution and a maximum temperature of 145.5 °C. Additionally, an electro-thermal conversion efficiency (hr+c) of 17.05 mW (°C cm2)−1 is achieved. Finally, a comparative Life Cycle Assessment with FR-4 based electronics has been undertaken and the environmental impacts are calculated. The impact assessment shows a two magnitude lower impact on the environment for most categories, which suggests the approach is beneficial for the environment at a global production level. The results show that the photothermal pyrolysis of Kraft paper using a laser diode allows for low-impact devices flexible and green electronics products.
Keywords: flexible resistive heater; kraft paper; laser-induced graphene; paper electronics; sustainable electronics